Economics of potato (Solanum tuberosum L) production in Taplejung district of Nepal - Timsina, KP; Kafle, K; Sapkota, S (Agronomy Journal of Nepal, 2013)
Potato is staple crop of high hills in Nepal. It is one of the important crops to address food insecurity in the country. A study on economics of potato production was conducted in Fungling, Dokhu, Nangkholang and Hangdewa VDCs of Taplejung district in September 2010. Altogether 180 potato producers from 13 farmers’ group, which received the membership of Commercial Agriculture Alliance (CAA), were taken as sample of the study by using purposive sampling technique. The regression analysis showed that income from potato has significant contribution (P<0.01) to total income from High Value crops (HVCs). Around 90 percent farmers in the study area were using improved varieties of potato seed such as Desiree, Kufrijoti and Cardinal. The correlation between lowland and upland growers was weakly related (r= 0.18). Average area per household for potato production and its productivity was found 0.75 Ropani and 844 Kg/Ropani, respectively. The cost of production per Kg potato was NRs. 7.3. Means of transportation to district headquarter was by human labor and its cost ranged from NRs. 2-5 per Kg. The transportation cost from Taplejung to Birtamod market was found in between NRs 4-6 depending upon season. Gross margin of potato per Ropani was NRs.15504 and the benefit cost ratio was 2.9.The highest average price of potato (NRs. 32.5 per Kg) at Birtamod wholesale market at nearby terai was found in September to October, whereas the highest average price of potato (NRs. 38.7 per Kg) at Taplejung market was found in May to June. Findings revealed that access to collection centre, credit facilities, storage facilities and weak backward and forward linkage were the major problems in the study area, whereas suitability of climate, availability of improved technology, improving access to road, and communication were the major strengths for potato production in the district. Findings indicated that there was a high potentiality of commercial potato production and ensuring food security in Taplejung district, however, it will be necessary to suitably adjust by creating time and place utility in future. DOI: http://dx.doi.org/10.3126/ajn.v2i0.7533 Agronomy Journal of Nepal (Agron JN) Vol. 2: 2011 pp.173-181